Exclusive Breast Milk An Effort to Prevent Stunting Events: A Literature Review - Diksi Laksmita Dewi; Sri Rahayu; Noviyati Rahardjo Putri; Isnu Kurnia Nugrahaeni (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
Based on data from the World Health Organization (WHO), Indonesia is the third country with the highest prevalence of stunting under five in Southeast Asia in 2005-2017 of 36.4%. Stunting toddlers is a predictor of poor quality of human resources that can reduce productive abilities in the future. One of the influencing factors is exclusive breastfeeding and bad parenting practices. Objective: The purpose of this article is to describe the effectiveness of exclusive breastfeeding from birth on the prevention of stunting. This article uses a literature review method with keywords; stunting, exclusive breastfeeding, risk factors for stunting, determinants of stunting. The online resources used include; PNRI, Science Direct, PubMed, Elsevier and Google Scholar. The results showed that exclusive breastfeeding could reduce the incidence of stunting. Breast milk fulfills the needs of macronutrients and micronutrients for infants for 6 months. Long-chain unsaturated fatty acids are very beneficial for the development of brain cells so that babies become intelligent. These ingredients include DHA (Decosahexanoic Acid) and Arachidonic Acid (AA). In 100 ml grams of breast milk, it contains 62 kcal of energy, 1.5 grams of protein, 3.2 grams of fat, 7.0 grams of carbohydrates, 34 mg of calcium and 0.2 mg of Fe. Exclusive breastfeeding from birth is an effort to prevent stunting. These efforts target breastfeeding mothers and children aged 0-6 months, by encouraging early initiation of breastfeeding (feeding with breast milk/colostrum), and encouraging exclusive breastfeeding. Keywords: stunting; exclusive breastfeeding; content of exclusive breastfeeding; prevention of stunting.